Early myocardial impairment in type 1 diabetes patients without known heart disease assessed with tissue Doppler echocardiography: The Thousand & 1 study. (July 2016) - Jensen, Magnus Thorsten; Sogaard, Peter; Andersen, Henrik Ullits; Gustafsson, Ida; Bech, Jan; Hansen, Thomas Fritz; Theilade, Simone; Almdal, Thomas; Rossing, Peter; Jensen, Jan Skov
Purpose: Cardiovascular disease is the most common cause of mortality in type 1 diabetes; patients with albuminuria are at greatest risk. We investigated myocardial function and premature myocardial impairment in type 1 diabetes patients with and without albuminuria compared to controls. Methods: This study included a cross-sectional survey of 1093 type 1 diabetes patients from Steno Diabetes Center and 200 healthy controls. Conventional and tissue Doppler echocardiographic measurements were analysed in multivariable models in normoalbuminuria ( n = 760), microalbuminuria ( n = 227) and macroalbuminuria ( n = 106). Investigators were blinded to degree of albuminuria. Results: For the type 1 diabetes patients, mean age was 49.6 years, 53% were men and mean diabetes duration was 25.5 years. In multivariable models systolic velocity s ′ did not differ between type 1 diabetes patients with normoalbuminuria and controls (β-coefficient [95% confidence interval]: −0.17 [−0.41; 0.08], p = 0.19), but was impaired between controls and microalbuminuria (−0.53 [−0.84; −0.23], p = 0.001) and macroalbuminuria (−0.59 [−0.96; −0.22], p = 0.002). Diastolic measurements ( e ′, a ′, e ′/ a ′, and E / e ′) were all significantly impaired in type 1 diabetes, for example, e ′/ a ′: normoalbuminuria, microalbuminuria and macroalbuminuria versus controls: −0.38 [−0.52; −0.23], p < 0.001; −0.49 [−0.67; −0.32], p < 0.001; and −0.81 [−1.03; −0.59], p < 0.001. In age-related analyses, myocardial impairment occurred prematurely in type 1 diabetes compared to controls (e.g. E / e ′ = 8; 9.2 years [normoalbuminuria], 17.3 years [microalbuminuria] and 41.4 years [macroalbuminuria] prematurely, respectively). Conclusion: In type 1 diabetes patients with albuminuria, both systolic and diastolic functions are impaired, whereas in patients without albuminuria only diastolic function is affected. Myocardial impairment is detectable many years prematurely in type 1 diabetes, especially in patients with albuminuria.